USE OF SUPERO-TEMPORAL FREE CONJUNCTIVO-LIMBAL AUTOGRAFT IN THE SURGICAL MANAGEMENT OF PTERYGIUM: OUR TECHNIQUE AND RESULTS - Sadiq, Muhammad Naqaish; Arif, Abdus Salam; Jaffar, Sulman; Bhatia, Jagdish (Journal of Ayub Medical College Abbottabad, 2009)
Background: A pterygium is a fibro-vascular, wing shaped encroachment of the conjunctiva on to the cornea. The prevalence rates ranges from 0.7 to 31% among different populations and also influenced by age, race, and exposure to solar radiations. Ultraviolet light-induced damage to the limbal stem cell barrier with subsequent conjunctivalisation of the cornea is the currently accepted aetiology of this condition. Indication of surgery include visual impairment, cosmetic disfigurement, motility restriction, recurrent inflammation and interference with contact lens wear. This Study was conducted to know the safety, efficacy and success with supero-temporal free conjunctivo-limbal auto graft transplantation in the surgical management of pterygium. Methods: Prospective case series where supero temporal free conjunctivo-limbal auto grafting was performed on 72 eyes of 72 patients with vascular progressive pterygia. Pterygium recurrence was considered a surgical failure. Recurrence was defined as fibro vascular tissue crossing the corneo-scleral limbus on to the clear cornea in the area of previous pterygium excision before 6 months. Results: Recurrence of pterygium was noted in three out of 72 eyes (4.16%), after a minimum follow up of 12 months to maximum of 25 months (Mean 14.6 months). No major intra-operative or postoperative complications were encountered. Conclusion: Supero temporal free conjunctivo-limbal auto graft appears to be a safe and effective technique in the surgical management of pterygium. The inclusion of limbal tissue in the conjunctival auto graft following pterygium excision appears to be essential to ensure low recurrence rate. Keywords: Conjunctival auto graft, limbal transplantation, pterygium, recurrence